Effect of putative probiont Enterococcus hirae on the hematological parameters of juvenile African catfish, Clarias gariepinus (Burchell, 1822) during pre- and post-challenge against Aeromonas hydrophila - Hamid, Nur Hidayahanum; Mohd Daud, Hassan; Srisapoome, Prapansak; Abu Hassim, Hasliza; Mohd Yusoff, Md Sabri; Kayansamruaj, Pattanapon; Hamdan, Ruhil Hayati; Mohd Yusoff, Siti Fairus; Abu Bakar, Siti Nadia (Penerbit UTM Press, 2018)
Probiotics have been widely known to have the ability to improve the immune system of livestock and aquatic animal. The present study was carried out to evaluate the effect of dietary supplementation of Enterococcus hirae UPM01 (E1) and UPM02 (E2) on hematological parameters of juvenile African catfish, Clarias gariepinus during pre- and post-challenge with fish pathogen, Aeromonas hydrophila. The probiotics were previously isolated from vegetable wastes which have been fermented for 7 days. The experimental fish (270 tails) with an average weight of 5.13 ± 1.03 g were distributed and divided randomly into 3 groups (Control (CTRL), E1 (108 CFU/ml) and E2 (108 CFU/ml).The feeding trial was conducted for 50 days. All experimental groups were then challenged with A. hydrophila (1.5 × 106 CFU/mL) via intraperitoneal injection on day 51st. Prior to challenge, blood samples were collected randomly from five fish from each group on day 51st (pre-challenge). After 72 hrs of post-challenge, blood samples were again collected from five fish from each group. The hematological parameters such as total erythrocyte count (RBC), total leucocyte count (WBC), packed cell volume (PCV), hemoglobin (Hb), mean corpuscular volume (MCV) and corpuscular hemoglobin concentration (MCHC) were examined. Hematological profiles of pre- and post-challenge infected juvenile catfish were compared with the control group. The RBC, Hb, WBC, PCV, MCV and MCHC of fish fed with probiotics showed significant difference (P<0.05) as compared to control group during pre- and postchallenge of pathogen. The high level of RBC and WBC during pre- and post-challenge showed the capability of the probiotics to improve the immune responses of juvenile African catfish and thus increased the fish disease resistance against A. hydrophila infection. The result suggested that both E. hirae UPM01 and UPM02 could be used effectively as a probiotics in aquaculture.